REMOVED: Breaking resistance to nanoantibiotics by overriding corona-dependent inhibition using a pH-switch. (June 2019) - Siemer, Svenja; Westmeier, Dana; Vallet, Cecilia; Steinmann, Jörg; Buer, Jan; Stauber, Roland H.; Knauer, Shirley K.
Abstract : This article has been removed: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been removed at the request of the Editors. Parts of Figure 1 were obtained in conjunction with another group of researchers. This group does not wish to publish this data as part of this manuscript. As this data has been deemed critical to the manuscript, and permission to publish the data has not been obtained, the manuscript has been removed. One of the conditions of submission of a paper for publication is that the authors have the right to publish the materials within. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not resolved prior to publication.